Tantangan ASEAN +3 - Yulius Mada Kaka (Universitas Kristen Satya Wacana, 2017)
This paper aims to show the negative potential that arises from regional agreements and describes the economic aspects of the Association of Southeast Nations Plus Three (ASEAN + 3). As for the formulation of problems, among others, the study of the forms of regional relations and the challenges facing ASEAN + 3. The formulation of the problem is then answered using the literature review method with descriptive explanation. The results show that regional relations in the present era are within the framework of new regionalism that has a similar pattern to the EU. Moreover, the conclusions gained through this study are the very diverse socio-economic conditions of Asia suggesting that there will always be interactions between democratic and non-democratic states, which involve not only the vast forces versus the small, but also the interstate and the situation poses a threat to ASEAN + 3 political integration.